ULTRASTRUCTURAL LOCALIZATION OF DIALYZED IRON-REACTIVE MUCOSUBSTANCE IN RABBIT HETEROPHILS, BASOPHILS, AND EOSINOPHILS - Hardin, J. H. (The Rockefeller University Press, 1971)
For ultrastructural localization of acid mucosubstances in rabbit granulocytes, bone marrow and buffy coat specimens were fixed with formalin, glutaraldehyde, or osmium tetroxide, sectioned at 40 µ, and stained with the Rinehart and Abul-Haj solution of dialyzed iron (DI). Heterophils revealed DI staining on the outer surface of the plasma membrane, in the Golgi complex involved in primary granulogenesis, and in primary granules. The intragranular distribution of DI-stained material varied at different stages in the maturation of primary granules. Immature granules of heterophils fixed by any of the three methods contained a peripheral concentric band of DI-positive material; however, fully mature primary granules possessed a core of DI-reactive material in heterophils fixed with osmium tetroxide, but they contained little or no staining in heterophils fixed with formalin or glutaraldehyde. Secondary granules of rabbit heterophils failed to stain with DI. Tertiary granules, observed only in late heterophils, contained distinct DI-positive particles. Basophil granules exhibited intensely DI-stained material distributed in an orderly pattern throughout the granule. In eosinophils, DI staining was localized in the Golgi complex and in the rims of a few immature cytoplasmic granules.